Peningkatan Hasil Belajar Tematik Terpadu Menggunakan Model Discovery Learning di Kelas V SDN 06 Kota Mukomuko - Sundaeni, Anis; Arwin, Arwin (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2024)
This study aims to improve student learning outcomes in integrated thematic learning using the Discovery Learning model in class V SDN 06 Mukomuko City. This type of Classroom Action research with qualitative and quantitative approaches. Consisting of two cycles with the stages of planning, implementing, observing, and reflecting. The research subjects were teachers and 15 fifth-grade students at SDN 06 Mukomuko City. The results showed that the RPP experienced an increase in cycle I with an average of 85% (B) in cycle II to 95% (SB). The assessment of the teacher aspect experienced an increase in cycle I with an average of 89.06% (B) and cycle II to 96.87% (SB). The assessment of student aspects experienced an increase in cycle I obtaining an average score of 87.5% (B) and cycle II to 93.75% (SB). Integrated thematic learning outcomes also increased the knowledge of cycle I obtaining an average score of 80.92 (B) and cycle II to 90.22 (SB). And the skills of the first cycle 80.09 (B), increased in the second cycle 92.22 (SB). So, the use of the Discovery Learning learning model can improve student learning outcomes in integrated thematic learning in class V SDN 06 Mukomuko City.